2010
DOI: 10.1371/journal.pone.0009431
|View full text |Cite
|
Sign up to set email alerts
|

Holographic Photolysis for Multiple Cell Stimulation in Mouse Hippocampal Slices

Abstract: BackgroundAdvanced light microscopy offers sensitive and non-invasive means to image neural activity and to control signaling with photolysable molecules and, recently, light-gated channels. These approaches require precise and yet flexible light excitation patterns. For synchronous stimulation of subsets of cells, they also require large excitation areas with millisecond and micrometric resolution. We have recently developed a new method for such optical control using a phase holographic modulation of optical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
55
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 50 publications
1
55
0
Order By: Relevance
“…It includes light paths for digital holography (purple path), epifluorescence illumination (blue path), and remote-focusing (green path). Generation of 3D multiple diffraction-limited spots for photolysis at 405 nm (18) is achieved using a conventional digital holography arrangement (12,17,19) through the principal objective O1 (SI Materials and Methods). Axial scanning is performed at a remote location to image in 3D without modifying the position of the photoactivation spots.…”
Section: Resultsmentioning
confidence: 99%
“…It includes light paths for digital holography (purple path), epifluorescence illumination (blue path), and remote-focusing (green path). Generation of 3D multiple diffraction-limited spots for photolysis at 405 nm (18) is achieved using a conventional digital holography arrangement (12,17,19) through the principal objective O1 (SI Materials and Methods). Axial scanning is performed at a remote location to image in 3D without modifying the position of the photoactivation spots.…”
Section: Resultsmentioning
confidence: 99%
“…Diffractive wavefront shaping techniques including computergenerated holography (CGH) and generalized phase contrast are an emerging tool for dynamic patterned photo-excitation [20][21][22][23] that were shown to allow structured two-(2D) and threedimensional (3D) excitation of dendritic arbors 20,24 and neurons 25 using neurotransmitter photolysis as well as twophoton optogenetic stimulation of several neurons in brain slices 26 . The principle advantage of CGH systems 22,23 is that they naturally combine the high intensity, efficiency and resolution that are characteristic of sequential laser deflection methods (such as acousto-optical deflectors) with the capacity for scan-less simultaneous parallel illumination of multiple locations of microdisplay array projectors, but without their respective limitations.…”
mentioning
confidence: 99%
“…That is, unlike digital mirrors and other array microdisplays, CGH divides power among the 'on' stimulation pattern and avoids the massive inefficiency resulting from blocking the light to the large proportion of 'off' pixels (typically 4 490%), and unlike laser deflectors, the patterns are projected simultaneously rather than sequentially, and are thus independent of (the relatively long) dwell times. Although CGH has multiple advantageous properties as a photo-stimulation tool, previous direct demonstrations of single-photon CGH were limited to neurotransmitter photolysis in brain slices 20,24,25 and were strongly limited in their speed, stimulation field (SF) area and number of simultaneously activated neurons.…”
mentioning
confidence: 99%
“…In order to block the zero-order non phase-modulated component reflected from the SLM, we introduced a defocus in the beam by adjusting the distance between L BE1 and L BE2 in order to displace the zero-order focus by 30 to 40 mm after the Fourier plane of the first lens. 17,18 For the diffracted first order, the defocus was compensated with a spherical Fresnel lens at the SLM. Thus, with the zero-order displaced 30 to 40 mm from the effective Fourier plane of L 1 , we could block the unwanted zero-order component with a point block [ Fig.…”
Section: Computer-generated Holographymentioning
confidence: 99%
“…Lutz et al 26 demonstrated that the simulations faithfully predict the experimentally measured propagation of shaped, CGH-generated spots. Although these simulations do not factor in depth-dependent brain tissue scattering, Zahid et al 18 have shown that holographic spots maintain axial confinement at depths of 30 μm in hippocampal slices. The axial confinement of the simulated beam propagation was quantified as full width at half maximum (FWHM) of intensity averaged over the "dendrite shaped" region of interest (ROI) in each axial plane [ Fig.…”
Section: Axial Propagation Simulationsmentioning
confidence: 99%